Obtenção de carbonato de glicerol assistida por ultrassom e síntese de inibidor de incrustação biodegradável - Silva, Silvia Shelly Otaviano da (2023)
The production of glycerol carbonate through the transesterification reaction between a source of triglyceride and dimethyl carbonate (DMC) has been increasingly investigated, as it enables the generation of biodiesel and glycerol carbonate, in which the latter presents several active sites, is shown as a very reactive molecule, providing a wide range of applications. Among these applications, there is the generation of scale inhibitors, in view of the current need for nitrogen and phosphorus-free products that are potential causes of eutrophication processes in water bodies. In this study, the parameters of the ultrasound (used as an intensifier of the reaction process) were initially evaluated considering 0.5 of cycle and a variation of 0 - 100% of frequency, for the transesterification reaction, aiming at obtaining biodiesel and glycerol carbonate. Next, the reaction conditions were analyzed, varying the molar ratio of coconut oil (triglyceride): DMC (1:4 – 1:8), catalyst load (sodium methoxide) (1-5%). After obtaining glycerol carbonate, it was applied in the step of opening the epoxide ring of methyl ricinoleate. The reactions were conducted by means of CCD plajenamento, using niobium phosphate (NbOPO4) as catalyst, for the following conditions, the variation of molar ratio epoxide:glycerol carbonate (1:1 – 1:3), temperature (80 – 120 °C) and catalyst loading (1 – 1.5% w/w), the reaction time was fixed at 24h. Finally, the performance of the inhibitor was evaluated for a variation of 500 to 2000ppm of inhibitor, between 0 - 240 min. The FAME content and carbonate selectivity were evaluated by Gas Chromatography (GC), for which the best results obtained were for a FAME content of 70.68% and selectivity of 80.22% for glycerol carbonate. The evaluation of the epoxidation reaction and opening of the epoxide ring was validated using Fourier Transform Infrared Spectroscopy (FTIR), Nuclear Magnetic Resonance (NMR) and acidity index, making it possible to obtain 100% opening of the epoxide ring, when evaluating the C-O bond referring to the epoxide (AFTIR (C-O-C)). The efficiency of the scale inhibitor produced was evaluated through batch tests using a synthetic brine, rich in calcium carbonate, in which the results of turbidity lower than 10 NTU were evaluated, proving the good performance of the developed inhibitor.